Plant growth promoting and antifungal asset of indigenous rhizobacteria secluded from saffron (Crocus sativus L.) rhizosphere. (January 2021) - Rasool, Akhtar; Imran Mir, Mohammad; Zulfajri, Muhammad; Hanafiah, Marlia Mohd; Azeem Unnisa, Syeda; Mahboob, Mohammed
Abstract: Saffron ( Crocus sativus L.) is an important plant in medicine. The Kashmir Valley (J&K, India) is one of the world's largest and finest saffron producing regions. However, over the past decade, there has been a strong declining trend in saffron production in this area. Plant Growth Promoting Rhizobacteria (PGPR) are free living soil bacteria that have ability to colonize the surfaces of the roots and ability to boost plant growth and development either directly or indirectly. Using the efficient PGPR as a bio-inoculant is another sustainable agricultural practice to improve soil health, grain yield quality, and biodiversity conservation. In the present study, a total of 13 bacterial strains were isolated from rhizospheric soil of saffron during the flowering stage of the tubers and were evaluated for various plant growth promoting characteristics under in vitro conditions such as the solubilization of phosphate, production of indole acetic acid, siderophore, hydrocyanic acid, and ammonia production and antagonism by dual culture test against Sclerotium rolfsii and Fusarium oxysporum . All the isolates were further tested for the production of hydrolytic enzymes such as protease, lipase, amylase, cellulase, and chitinase. The maximum proportions of bacterial isolates were gram-negative bacilli. About 77% of the bacterial isolates showed IAA production, 46% exhibited phosphate solubilization, 46% siderophore, 61% HCN, 100% ammonia production, 69% isolates showed protease activity, 62% lipase, 46% amylase, 85% cellulase, and 39% showed chitinase activity. Three isolates viz., AIS-3, AIS-8 and AIS-10 were found to have the most plant growth properties and effectively control the growth of Sclerotium rolfsii and Fusarium oxysporum . The bacterial isolates were identified as Brevibacterium frigoritolerans (AIS-3), Alcaligenes faecalis subsp . Phenolicus (AIS-8) and Bacillus aryabhattai (AIS-10) respectively by 16S rRNA sequence analysis. Therefore, these isolated rhizobacterial strains could be a promising source of plant growth stimulants to increase cormlets growth and increase saffron production. Graphical abstract: PGPR design of indigenous rhizobacteria isolated from saffron rhizosphere ( Crocus sativus L.). Image 1 Highlights: The PGPR as a bioinoculant is an alternative practice for improving agricultural quality and production. Indigenous rhizobacteria secluded from Saffron rhizosphere were evaluated for various plant growth activities with antifungal properties against Sclerotium rolfsii and Fusarium oxysporum . 13 bacterial strains were isolated from rhizospheric soil of Saffron and their plant growth-promoting properties were studied. Three potential PGPR (AIS-3, AIS-8, and AIS-18) were identified by 16S rRNA sequence analysis as the most valuable rhizobacteria.